(3efgGL GdJMbjb heMGSf GdJdajb aj CUhd GdOjfs - (3jMji Hf MSf Hf ehSi GdbQTis
(3ChdgG (B:s
(3GdMeO ddg GdOGd Ydi PGJg hUaGJg CeG HYO , aEf Cge GdJcdja Yde GdYbGFO , hEf GdXaQ ajg HGdMb ajg ef CLd GdahGFO s
(3BNQgG (B:s
(3hGdCUd YOe GdLhGR hGdMeO ddg hMOg , Je GdcJGH Hef Gddg hdWag hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjjf HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds